Properties of ceramics prepared using dry discharged waste to energy bottom ash dust. Issue 9 (September 2015) - Bourtsalas, Athanasios; Vandeperre, Luc; Grimes, Sue; Themelis, Nicolas; Koralewska, Ralf; Cheeseman, Chris
The fine dust of incinerator bottom ash generated from dry discharge systems can be transformed into an inert material suitable for the production of hard, dense ceramics. Processing involves the addition of glass, ball milling and calcining to remove volatile components from the incinerator bottom ash. This transforms the major crystalline phases present in fine incinerator bottom ash dust from quartz (SiO2 ), calcite (CaCO3 ), gehlenite (Ca2 Al2 SiO7 ) and hematite (Fe2 O3 ), to the pyroxene group minerals diopside (CaMgSi2 O6 ), clinoenstatite (MgSi2 O6 ), wollastonite (CaSiO3 ) together with some albite (NaAlSi3 O8 ) and andradite (Ca3 Fe2 Si3 O12 ). Processed powders show minimal leaching and can be pressed and sintered to form dense (>2.5 g cm -3 ), hard ceramics that exhibit low firing shrinkage (<7%) and zero water absorption. The research demonstrates the potential to beneficially up-cycle the fine incinerator bottom ash dust from dry discharge technology into a raw material suitable for the production of ceramic tiles that have potential for use in a range of industrial applications.